Perceptions of Teachers Regarding Early Childhood Classroom - Abdullah; Dr. Hafiz Muhammad Irshadullah; Dr. Saqib Shahzad (Dialogue Social Science Review (DSSR), 2025)
Perceptions of Teachers regarding Early Childhood Classroom were a new study. In this the following objectives were used: (1) To investigate teachers’ views about early childhood classroom; and (2) To find out the teachers’ opinion about students learning at early childhood classroom. While in this study two research questions were tested: (1) What do educators think the best setting is for young children to learn? and (2) How do teachers perceive the current situation of their school's early childhood classrooms? All the Primary School Teachers in Ghari Kapoora were the population in this study. A sample of (63) Primary School Teachers from (10) Schools were selected randomly. A closed-ended questionnaire with three (Yes, No, & Undecided) were developed. The instrument was validated from the experts. Reliability of instrument was calculated 0.80. It was concluded that most of the teachers were of the view that ECC refers to learning from birth to eight years, produces a child’s brain is more responsive, and productive. Based on conclusion, it was recommended that teachers may be focused on Early Childhood Classroom in their learning.